Regional heterogeneity in occupational change: Using Census data to investigate employment polarisation and upgrading at NUTS-3 level - Esperanza Vera-Toscano; Marta Fana; Enrique Fernández-Macías (European Commission, Joint Research Centre (JRC), 2022)
Using Census data, this paper proposes an empirical approach to look at differences and changes in the composition of employment across NUTS-3 level regions of six European Union countries over the period 1981 - 2011. We focus on jobs (defined as specific occupations within specific sectors) as our unit of analysis. We rank all jobs based on their average educational level and divide these distribu-tions into terciles. We accommodate the approach to compare regions to their national average and see how they evolve compared to the national trend. Our aim is to determine if regional employment structures converge over time and whether they are polarising, upgrading or downgrading. Several hypotheses regarding possible underlying factors of structural changes are further discussed. Results show a high degree of heterogeneity in the different regions. This presents considerable challenges for policymakers, as they need to gear their efforts at regional, more localised level.
Keywords: 330; Job polarisation; economic restructuring; technological change; Census data; regional heterogeneity